Prevalence of Spontaneous Delivery and Cesarean Section in Pregnant Patients with Myopia at Pregnancy Clinic Dr. Soetomo General Academic Hospital, Surabaya - Rosalia Adriani Malika; Ernawati Ernawati; Prillia Tri Suryani (Universitas Airlangga, 2023)
Highlights:1. The selection of delivery methods in pregnant patients with myopia is needed to prevent blindness.2. Although there was no report of retinal detachment either in spontaneous delivery or in cesarean section in this study, all pregnant patients with pathologic myopia or peripheral retinal degeneration should be consulted by Ophthalmologist. AbstractIntroduction: The selection of delivery methods in pregnant patients with myopia is needed to prevent blindness. This study aimed to calculate spontaneous delivery and cesarean section prevalence in pregnant patients with myopia.Methods: This was a descriptive epidemiology study using medical records of Maternity Outpatients Dr. Soetomo General Academic Hospital, Surabaya, from September 2012 to September 2014. Age, stage of myopia, and delivery method data were taken. The sample in this study was all pregnant patients with myopia, as many as 30 patients.Results: Forty percent of pregnant patients with myopia were in the 21-25 age group. There were three patients with low myopia (10%), seven patients with moderate myopia (23.33%), and 20 patients with high myopia (66.66%). More than half of the pregnant patients with myopia had a cesarean section (66.66%), and ten had a vaginal delivery (33.33%). The most indications of cesarean sections were non-myopia in 14 patients (70%), and only six indicated myopia (30%). Myopia was not a primary indication for cesarean sections in Maternity Outpatients Dr. Soetomo General Academic Hospital, Surabaya.Conclusion: Although there was no report of retinal detachment either in spontaneous delivery or in cesarean section in this study, all pregnant patients with pathologic myopia or peripheral retinal degeneration should be consulted by an Ophthalmologist.